The Korean restaurant : a services marketing failure? - O'Brien, Justin, active 2019 (London : SAGE Publications: SAGE Business Cases Originals, 2019)
This case is designed to offer digital and services marketing students the opportunity to investigate the experiential and ethical dimensions of a dissatisfactory service: Jay and Veekay's underwhelming family dining experience in an unfamiliar restaurant. The case explores the real, but anonymised, protagonist's unsuccessful attempt to select a new culinary experience using an electronic word-of-mouth tool. The meal service was particularly disappointing, and Jay has to consider what to do next. By flipping from the customer to service provider perspective, students are also invited to consider how the restaurant owners might attempt to mitigate any reputational damage on social media caused by failing to meet customer expectations.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Ethnic restaurants -- Marketing -- Case studies; Advertising -- Restaurants -- Case studies; Ethnic restaurants -- Internet marketing